Speech and Language Therapy students' experience of Peer Assisted Learning: an undergraduate dissertation project - Anne Guyon (Association for Learning Development in Higher Education (ALDinHE), 2015)
The implementation of Peer Assisted Learning (PAL) on healthcare courses in Higher Education has been explored in a number of studies. This paper presents peer research conducted by final year undergraduate Speech & Language Therapy students into the experience of PAL mentees and mentors on the same course. The focus was on the effects of PAL on academic and professional development. Data were generated from standard PAL evluations and focus groups. Findings indicate that mentees benefit from PAL in terms of their university experience and learning. Engagement with PAL results from its structured yet informal nature and the enthusiasm of the mentors. The collaborative nature of PAL took time to develop, impacting on the behaviours of the mentees and mentors. All participants commented on gaining from PAL. Overall PAL offers mentees and mentors opportunities which enhance their academic learning and professional development.